Measuring the Community Satisfaction Index (CSI) among the beneficiaries of the CSR Program by PT Pertamina Patra Niaga DPPU Syamsudin Noor - Faidah Ramadhani; Gina Febryana Nurhaliza; Nazwa Anisya (PT. Hanken SUkses Jaya, 2023)
This study focuses on measuring the Community Satisfaction Index (CSI) among the beneficiaries of the Corporate Social Responsibility (CSR) Program conducted by PT Pertamina Patra Niaga DPPU Syamsudin Noor. The objective of the research is to assess the level of satisfaction and contentment within the community resulting from the CSR initiatives. The study employs a mixed-methods approach, combining quantitative surveys and qualitative interviews to gather comprehensive data. The findings contribute to a better understanding of the effectiveness of the CSR program in generating positive impacts and fostering community satisfaction. The research outcomes hold significance for both PT Pertamina Patra Niaga and other organizations aiming to enhance their CSR endeavors for maximum community benefit and contentment